Comparative Study of Different Spectrophotometric Methods for Determination of Phenazopyridine Hydrochloride in the Presence of its Oxidative Degradation Product. Issue 6 (1st November 2016) - Attia, Khalid A.M.; El-Abasawi, Nasr M.; El-Olemy, Ahmed; Abdelazim, Ahmed H.
Abstract: Four stability indicating spectrophotometric methods have been developed for selective determination of phenazopyridine hydrochloride (PAP) in the presence of its oxidative degradation product 2, 3, 6-triaminopyridine (TAP). The described spectrophotometric methods namely; first derivative ( 1 D), ratio difference spectrophotometric method (RDSM), first derivative of ratio spectra ( 1 DD, and dual wavelength (DW). For 1 D method, the peak amplitudes at 370 nm were measure, while the difference between 428 and 276 nm in peak amplitudes were measured for RDSM. On the other hand, the peak amplitudes at 360 nm were measured for 1 DD, while the difference in the absorbance between 425 and 256 nm were measured for DW. The regression analysis data for the calibration plots of PAP showed a good linear relationship over the concentration range of 1-14 μg/ml by the four proposed methods. The proposed methods have been successfully applied to the assay of PAP in pharmaceutical formulation. Also, the obtained results have been statistically compared to a reported HPLC method to give a conclusion that there is no significant difference between the investigated methods and the reported one with respect to validation parameters.